Late effects of treatment in survivors of childhood acute lymphoblastic leukaemia - Roux, Paul (Department of Paediatrics and Child Health, 2023)
Long-term survival and probable cure have become norms in acute lymphoblastic leukaemia of childhood. The adverse effects of treatment for leukaemia are diverse and complex. In many cases, treatment effects come to light 1 ong after the end of therapy. These so-ca 11 ed 1 ate effects (which are yet obscure and incompletely understood) have become increasingly important as the number of children surviving leukaemia increases. This thesis describes a comprehensive study of leukaemia survivors attending the Oncology Clinic of the Red Cross War Memorial Children's Hospital. The study sample consisted of all leukaemia survivors in long-term remission, disease free and off treatment up to January 1st, 1984. The study is introduced by a chapter which describes acute lymphoblastic leukaemia and pays particular attention to the effects of the primary disease on organs which may subsequently exhibit late effects of treatment. Treatment of acute lymphoblastic leukaemia is described in some detail and the reasons for current treatment strategies are outlined. Individual modalities of treatment are then discussed with reference to their mechanisms of action and potential for damage to non-neoplastic tissue. The study then examines all systems likely to have been damaged during therapy, in order to achieve a comprehensive impression of the late effects of leukaemia treatment. In each chapter, pertinent literature was reviewed up to January 1987. Growth is a major task of childhood. Many chronic diseases are potential causes of growth failure. A longitudinal retrospective study showed that statured growth in leukaemia survivors was stunted during treatment. Catch-up growth did not occur at the end of treatment, although normal growth velocity was resumed. Adult height was expected to be reduced as a result. In addition to temporary stunting of statured growth, leukaemia survivors showed a progressive increase in weight-for-height during treatment. This trend continued after treatment had ended. These changes in weight and height were peculiar to leukaemia survivors. Control groups of children with solid tumours in long term remission showed less stunting during treatment and had catch-up growth after treatment, except when they had undergone spinal i rradi ati on. Normal endocrine function is a prerequisite for normal growth and development. Although growth hormone responses to insulin-induced hypoglycaemia were frequently and significantly abnormal in survivors of childhood leukaemia, these children grew normally once treatment had stopped. Impaired growth hormone secretion appeared to be a marker of hypothalamic damage caused by leukaemia therapy. Testicular and ovarian function was normal in the absence of irradiation of these organs. Thyroid function was normal in leukaemia survivors although a minority showed evidence of hypothalamic damage in their response to thyrotropin releasing hormone. Normal prolactin levels in children showing other hormonal evidence of hypothalamic damage were thought to indicate the selectivity of damage caused by leukaemia treatment. Adrenal control and function were normal in leukaemia survivors. In the absence of a growth disorder, only thyroid status may need long-term assessment in leukaemia survivors. Intellectual development is a further major task of childhood. A sibling-controlled study of intellectual function indicated an intelligence deficit in children surviving leukaemia and its treatment. This deficit was thought to be the consequence of therapy, since children surviving solid tumours showed no such deficit in comparison with their sibling controls. Survivors of childhood leukaemia also had an increased incidence of visual perceptual difficulty and more school prob 1 ems than survivors of solid tumours, particularly in early primary grades. Intellectual outcome and school performance in leukaemia survivors may be improved by early visual perceptual training. Children surviving acute lymphoblastic leukaemia had significantly more minor motor abnormalities than children surviving solid tumours. Minor motor abnormalities were frequently and significantly associated with abnormalities of the brain visualized by computerized tomography. Neurophysiologic measurement (EEG, VER, BAER) did not contribute to the assessment of neurological outcome and correlated poorly with clinical and CT scan findings. A functional assessment of neurological outcome in leukaemia survivors should include a clinical examination for minor motor dysfunction. Some children manifested other organ-specific damage due to chemotherapy or radiotherapy. These isolated cases are discussed in the form of case reports and literature reviews. Patients have received treatment with cytotoxic drugs in addition to standard leukaemia therapy need to be followed for treatment-specific late effects. The psychological outcome of leukaemia survivors was assessed by means of parent interviews and teacher questionnaires. In terms of a low frequency of behaviour problems reported by these observers, psychosocial adaptation in leukaemia survivors vas surprisingly good. Children surviving solid tumours and healthy school children from the same community (the latter from a literature report) had similar frequencies of behavioural problems. In both leukemic children ana solid tumour control patients, certain patterns of family behaviour ~ere predictive of a poor psychological outcome. It appears that an early family assessment may identify families 'at risk'. If needs to be shewn whether such families would benefit from professional psychological support. In the final chapter a 'functional deficit score' is offered as a measure of overall outcome in terms of late effects of therapy. Patients were rated in five categories (growth, intellectual outcome, neurological status, miscellaneous organ damage and psychosocial adaptation) according to the severity of persistent late effects. Children surviving acute lymphoblastic leukaemia were shown to have been more seriously damaged by their treatment than children surviving solid tumours. The difference in overall damage was the consequence of central nervous system injury. Available evidence indicates that this central nervous system injury is caused by radiotherapy (with or ·thought a synergistic effect with i intrathecal 1 methotrexate) given as central nervous system 'prophylaxis'. With few exceptions, leukaemia survivors in this study had received L400 rads of deep x-ray therapy as cranial irradiation. This dosage has since been reduced world-wide. Current cranial irradiation 'prophylaxis' consists of 1800 rad of megavoltage radiotherapy. Fa 11 ow-up studies of survivor cohorts given such radiotherapy should include the measures embodied in the 'functional deficit score' described above.